Effects of paliperidone extended release on functioning level and symptoms of patients with recent onset schizophrenia: An open-label, single-arm, flexible-dose, 12-months follow-up study. (August 2015) - Üçok, Alp; Saka, Meram Can; Bilici, Mustafa
Abstract Background: Response to antipsychotic treatment is better in the early stages of schizophrenia. Aims: The primary objective of this non-randomized, single-arm, multicenter clinical trial was to explore the response to treatment and safety of a flexible dose of paliperidone (mean = 6.42 mg/day) in patients with recent onset schizophrenia (< 3 years after the first episode/hospitalization). Methods: Severity of clinical symptoms was evaluated by the Positive and Negative Syndrome Scale (PANSS), functioning was assessed using the Global Assessment of Functioning (GAF) scale and the Personal and Social Performance Scale (PSP). Results: In a total of 85 patients enrolled, 80 patients were eligible. Total PSP score at baseline (50.2 ± 11.6) increased at all visits. Total PSP score was 65.4 ± 12.1 at month 12 (P < 0.001). GAF scores were significantly higher at all visits compared with baseline (P = 0.001). It was 62.4 ± 12.5 with an increase of 42.9% at month 12 (P < 0.001). PANSS Positive and Negative subscales and General psychopathology subscale scores showed significant reductions beginning with month 3 and were 11.9 ± 3.8 (29.3%; P < 0.001), 13.7 ± 5.6 (27.3% P < 0.001) and 27.8 ± 7.1 (23.2%; P < 0.001) at month 12, respectively. Twelve patients (14.3%) had a serious adverse event. The most common adverse events were insomnia (17.9%), nausea (8.3%), akathisia (4.8%), anxiety (4.8%) and depression (4.8%). Body weight values at the end of the study were significantly higher compared with baseline. Conclusion: The present study demonstrates that flexible dose of paliperidone resulted in a significant improvement in functioning and reduction in symptoms in patients with recent onset schizophrenia.